PENGARUH PERPUTARAN PIUTANG, LIKUIDITAS, SOLVABILITAS, DAN TOTAL ASSET TURNOVER TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUBSEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022–2025 - Dian Puspita Sari; Badrus Zaman; Andy Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of Receivable Turnover, Liquidity, Solvability, and Total Asset Turnover (TATO) on Financial Performance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2025 period. Financial performance is proxied by Net Profit Margin (NPM). This study employs an associative quantitative approach using secondary data obtained from annual financial reports. The sample was determined through purposive sampling, resulting in 17 companies with 68 observations (a four-year unbalanced panel). Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, coefficient of determination test, t-test, and F-test with the assistance of SPSS version 25. The results show that, partially, Receivable Turnover, Liquidity, and Solvability have no significant effect on Financial Performance, whereas Total Asset Turnover has a significant negative effect on Financial Performance. Simultaneously, all four independent variables significantly affect Financial Performance, with an Adjusted R Square of 0.270, indicating that 27.0% of the variation in Financial Performance is explained by the model, while the remaining 73.0% is explained by other factors outside the model. These findings imply that asset-utilization effectiveness should be a primary concern for management in efforts to improve firm profitability.